THE EFFECT OF ADDING RED BEANS AGAINST THE ORGANOLEPTIC PROPERTIES OF SUMBAWA HORSE MILK BEVERAGE PRODUCT - Reni Sofiyatin (Jurnal Kesehatan Prima, 2018)
Abstract: The objective of the study was to perceive the effect of adding red beans against the organoleptic characteristic of red beans and Sumbawa horse milk beverage product. The study was designed by a Complete Random Design (RAL). One factorial was to increase red beans with 5 treatments and each treatment was conducted 3 times replication. Data were analyzed utilizing one way ANOVA and proceeded by employing Tukey test. Bases on organoleptic test found that the delightful value of color and texture of beverage product was significantly difference (P<0,05) whereas, against smell and taste found that there was no a significant difference (p>0.05).Keywords: Red Bean; Sumbawa Horse Milk.